Pulmonary compliance and lung volume are related to terrestriality in Anuran Amphibians - Withers, Philip; Hedrick, M.; Drewes, R.; Hillman, S. (The University of Chicago Press, 2014)
Dehydration tolerance of anuran amphibians is directly related to their ability to mobilize lymphatic reserves, with more terrestrial species having more effective lymph mobilization dependent on specialized skeletal muscles acting directly on the lymph sacs and via pulmonary ventilation. Consequently, we tested the hypothesis that pulmonary compliance, lung volume, and femoral lymphatic sac volume were related to terrestriality-and, hence, lymph mobilization-for 18 species of aquatic, semiaquatic, or terrestrial anuran amphibians. Lung compliance and volume were significantly related to body mass, but there was no significant phylogenetic pattern. There were significant habitat-related patterns for mass-corrected and phylogenetically corrected residuals for these pulmonary variables. Femoral lymph volume was significantly related to body mass, with no significant phylogenetic pattern, and there was only a weak correlation for habitat with mass-corrected and phylogenetically corrected residuals. These results suggest that pulmonary volume and compliance are strongly related to terres-triality in anuran amphibians and are under significant selection pressure to enhance lymph mobilization, but lymph sac volume does not appear to have a major role in adaptation to terrestriality. © 2014 by The University of Chicago.